Why do they do it? Differences in high-intensity exercise-affect between those with higher and lower intensity preference and tolerance. (March 2020) - Box, Allyson G.; Petruzzello, Steven J.
Abstract: Evidence suggests high-intensity exercise results in a more negative affective response when compared to moderate- or low-intensity exercise. However, a large number of individuals continue participating in high-intensity exercise, in spite of these supposed declines in affective state. Purpose: Determine whether trait differences influence variability in exercise-affect for those with higher versus lower exercise intensity preference and/or tolerance, and determine the mediating relationship between traits, exercise behavior, and affective states. Methods: Undergraduates ( N  = 245, 20.3 ± 1.7 yrs, BMI = 23.7 ± 3.8, 60.8% female, 82% regular exercisers) completed the Preference for and Tolerance of the Intensity of Exercise Questionnaire. They then completed a 15-min high-intensity body-weight circuit (HIC), a walk, and a reading condition, where valence (via Feeling Scale), perceived physiological activation (via Felt Arousal Scale), and ratings of perceived exertion were taken prior to, every 3-min during, and 20-min post (P20) condition, while activity enjoyment was assessed immediately post. Results: Multivariate ANOVAs revealed significant differences ( p s  < 0.05) in valence between those with high versus low intensity preferences during HIC at minutes 3 ( d  = 0.615), 6 ( d  = 0.772), 9 ( d  = 0.659), 12 ( d  = 0.625), 15 ( d  = 0.632), and at P20 ( d  = 0.554), and for enjoyment following HIC ( d =  0.545), but not for walking or reading conditions. Conclusions: These findings suggest the intensity-preference trait influences how an individual feels during high-intensity exercise, but has less influence on affect during moderate/lower intensity activities. These differences may be predictive of whether an individual will continue high-intensity exercise programming. Highlights: Individuals with higher intensity exercise preference reported more pleasant valence during high-intensity exercise. Those with higher-intensity exercise preference reported similar valence between high- and light-intensity conditions. Exercise programming may be optimized by considering individual traits that result in exercise pleasure variability.